Applying Kolb's Model to a Nontraditional Preservice Teaching Practicum. (September 2017) - Burns, Amy; Danyluk, Patricia
This article reports on the initial findings of an ongoing study that will see six preservice teachers placed in a nontraditional practicum placement as part of their bachelor of education program. Reported here is the examination of emergent professionalism of the initial two preservice teachers during their nontraditional practicum placement on a housing construction site. Emergent professionalism is enacted when teachers shift their concerns from self to other, as described by Fuller. The findings are then examined from the perspective of Kolb's experiential learning model, including the concrete experience, observation of and reflection on that experience, formation of abstract concepts based upon the reflection, and testing of the new concepts. As a result of this analysis, new insights are shared regarding the ways in which preservice teachers develop their emergent professionalism through examination of the environment, multiple sources of feedback, interdisciplinary lessons, and a hands-on learning environment.